Open-Ended Learning Model Assisted by Student Worksheets on Creative Thinking Skills - Osco Parmonangan Sijabat; Injen Pardamean Butar-Butar (MIMBAR PGSD Undiksha, 2025)
Mathematics learning ideally employs interactive approaches to cultivate students’ critical and creative thinking skills. However, students’ creative thinking abilities remain relatively low due to monotonous instructional practices that do not provide sufficient opportunities for them to explore and develop their ideas freely. This study aims to examine the effectiveness of the Open-Ended learning model integrated with student worksheets in enhancing learners’ creative thinking skills. The research employed a quasi-experimental method using a non-equivalent pretest–posttest control group design. The sample was selected through cluster random sampling, and data were collected using a creative thinking skills test, which was analyzed through descriptive and inferential statistical techniques. The findings indicate that students who learned through the Open-Ended model supported by student worksheets demonstrated better improvement in creative thinking compared to those who received conventional instruction. The implementation of this model was shown to encourage students to think more actively, generate diverse solutions, and build confidence in expressing new ideas. The implications of this study highlight the importance of adopting open and challenging instructional strategies to foster students’ creativity and higher-order thinking skills more effectively.